Does Pediatric Body Mass Index Affect Surgical Outcomes of Lower-Extremity External Fixation?. Issue 4 (June 2015) - Fedorak, Graham T.; Cuomo, Anna V.; Otsuka, Norman Y.
Abstract : Background: Obese patients are highly prevalent in the pediatric orthopaedic surgeon's practice and obesity is an increasing issue in the United States. Increased body mass index (BMI) has been associated with increased complications in pediatric orthopaedic patients, but no study has looked specifically at external fixation. The purpose of this study was to determine whether obesity is a risk factor for increased complications in lower-extremity procedures requiring external fixation. Methods: A retrospective chart review was conducted of pediatric patients who underwent external fixation as definitive operative treatment for any condition at a tertiary care hospital over a 15-year period. Patients were grouped into normal weight, overweight, and obese based on Centers for Disease Control definitions. All orthopaedic complications were recorded. Results: A total of 208 patients with a mean age of 11.2 years were identified. Ninety-four children were obese at the 95th percentile BMI or higher, 22 were overweight and 93 were normal weight. External fixation was applied to the tibia in 82 cases, to the femur in 77 and to both in 49. Mean duration of fixation was 160 days (range, 31 to 570 d) and patients were followed for a mean of 3.9 years (range, 1.0 to 12.0 y). There was no statistically significant difference in the rate of complications between the 3 groups ( P =0.61). In the obese group complications occurred in 68.1% versus 66.7% in the overweight group and 61.3% in normal weight. Conclusions: In the setting of external fixator use for lower-extremity pathology in pediatric patients, there is no association between an increase in complications and obesity as defined by BMI. Complication rates are high when external fixation is utilized for the lower extremity, however, patients and families should not be counseled that increased BMI will add to the burden of orthopaedic complications in this situation. Level of Evidence: Level II—prognostic.